Applying the building code : step-by-step guidance for design and building professionals : based on the 2015 International codes®, fifth edition /: step-by-step guidance for design and building professionals : based on the 2015 International codes®, fifth edition. ([2016]) - Geren, Ronald L, 1961-
No abstract available